O bloqueio dos receptores NMDA ou CRF1 no núcleo intersticial da estria terminal impede a ansiogênese induzida pela ativação nitrérgica do córtex pré-frontal medial e derrota social em camundongos - Faria, Matheus Pegoraro (Universidade Federal de São Carlos, 2019)
Nitric oxide (NO) release in the right medial prefrontal cortex (RmPFC) produces anxiogenesis. In the bed nucleus of the stria terminalis (BNST), a region that receives neuronal projections from the mPFC, NO also provokes anxiety, an effect that is blocked by local injections of corticotrophin-releasing factor type 1 receptor (CRF1) or n-methyld-aspartate receptor (NMDAr) antagonist. Anxiety is also enhanced by social defeat stress, and chronic stress impairs and facilitates, respectively, PFC and BNST roles in modulating behavioral responses to aversive situations. This study investigated whether the (i) chronic social defeat stress (CSDS) increases NO signaling in the mPFC; (ii) anxiogenic effects provoked by intra-RmPFC injection of NOC-9 (an NO donor) or by CSDS are prevented by intra-BNST injections of AP-7 (0.05 nmol) or CP 376395 (3.0 nmol), respectively, NMDAr and CRF1 antagonists, in male Swiss-Webster mice exposed to the elevated plus-maze (EPM). Results showed that (a) CSDS increased anxiety (i.e. reduced open-arm exploration) and repeatedly activated NOSn containing neurons, measured by ΔFosB (a stable nonspecific marker of neural activity) + NOSn double-labeling, in the right (but not left) mPFC, (b) NOC-9 in the RmPFC also increased anxiety and (c) both CSDS and NOC-9 effects were reversed by injections of AP-7 or CP 376395 into the BNST. These results suggest that NMDA and CRF1 receptors located in BNST play an important role in the modulation of anxiety provoked by NO in the RmPFC as well as by chronic social defeat in mice.
Anxiogenesis induced by social defeat in male mice: role of nitric oxide, NMDA, and CRF1 receptors in the medial prefrontal cortex and BNST
Keywords: CPFm; BNST; Óxido Nítrico; Dupla Marcação ΔFosB + NOSn; Receptores NMDA e CRF1; Camundongos socialmente derrotados; Ansiedade; mPFC; Nitric Oxide; ΔFosB + NOSn double-labeling; NMDA and CRF1 receptors; Socially defeated mice; Anxiety; CIENCIAS BIOLOGICAS::FARMACOLOGIA; CIENCIAS BIOLOGICAS::FISIOLOGIA; CIENCIAS DA SAUDE::FARMACIA; CIENCIAS BIOLOGICAS::FARMACOLOGIA::NEUROPSICOFARMACOLOGIA